2018
DOI: 10.1007/s11418-018-1243-5
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of Xiaoyao-jieyu-san on post-stroke depression and its potential mechanisms

Abstract: A stroke is a severe life-threatening disease with high fatality and disability rate. This investigation aimed to study the effect of Xiaoyao-jieyu-san (XYJY) on post-stroke depression (PSD) and its potential mechanisms. PSD rats were prepared using middle cerebral artery embolization (MCAO) and chronic unpredictable mild stress (CUMS), and divided into six groups (n = 10)-sham; MCAO; MCAO + CUMS (PSD); PSD + fluoxetine (1.84 mg/kg/day, 4 weeks); and PSD + XYJY (450 mg/kg/day and 900 mg/kg/day, 4 weeks). Body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…24 In our study, the combination of MCAO and CUMS caused weight loss in rats, which is consistent with previous studies. 25 EA intervention as well as fluoxetine ameliorated the loss of weight. The neurological score is commonly used to quantify the extent of neurological injury.…”
Section: Discussionmentioning
confidence: 88%
“…24 In our study, the combination of MCAO and CUMS caused weight loss in rats, which is consistent with previous studies. 25 EA intervention as well as fluoxetine ameliorated the loss of weight. The neurological score is commonly used to quantify the extent of neurological injury.…”
Section: Discussionmentioning
confidence: 88%
“…Wang et al suggested that JYP has an ameliorative effect on post-stroke depression in rats via modulating BNDF levels, cannabinoid receptors, and corticotrophin-releasing factor in ventral tegmental area-nucleus accumbens tissue. 93 Paeoniflorin, an active ingredient of PRA, can improve the depression-like behavior caused by chronic stress. This antidepressant effect may occur by regulating the functional activity of the hypothalamic-pituitary-adrenal (HPA) axis and increasing BDNF levels in the brain.…”
Section: The Pharmacological Mechanism Of Jyp In the Treatment Of Depmentioning
confidence: 99%
“…Several randomized controlled studies have shown that XYR alone or in combination with antidepressants can improve PSD symptoms [ 14 , 15 ]. Because few large-sample randomized controlled trials (RCTs) using XYR have been conducted on the PSD population, a reliable evidence-based basis regarding the use of XYR in treating PSD is still lacking.…”
Section: Introductionmentioning
confidence: 99%